High Ambient Temperatures Inhibit Ghd7-Mediated Flowering Repression in Rice. (11th September 2021) - Nagalla, Asanga Deshappriya; Nishide, Noriko; Hibara, Ken-ichiro; Izawa, Takeshi
Abstract: The anticipation of changing seasons is crucial for reproduction in plants. Despite the broad cultivation area, the effects of ambient temperature on photoperiodic flowering are largely unknown in rice. Here, we first examined flowering time under four distinct conditions: short-day or long-day and high or low temperature, using cultivars, nearly isogenic lines, and mutants in rice. We also examined gene expression patterns of key flowering-time genes using the same lines under various conditions including temporal dynamics after light pulses. In addition to delayed flowering because of low growth rates, we found that photoperiodic flowering is clearly enhanced by both Hd1 and Ghd7 genes under low-temperature conditions in rice. We also revealed that PhyB can control Ghd7 repressor activity as a temperature sensor to inhibit Ehd1, Hd3a and RFT1 at lower temperatures, likely through a post-transcriptional regulation, despite inductive photoperiod conditions. Furthermore, we found that rapid reduction of Ghd7 messenger RNA (mRNA) under high-temperature conditions can lead to mRNA increase in a rice florigen gene, RFT1 . Thus, multiple temperature-sensing mechanisms can affect photoperiodic flowering in rice. The rising of ambient temperatures in early summer likely contributes to the inhibition of Ghd7 repressor activity, resulting in the appropriate floral induction of rice in temperate climates.